Fitness Management: Role of coach support on effectiveness of Players - Dr Rakesh (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This paper addressed coaching management and the fitness management system. Due to the constant pressure from outside sources to win competitions, coaching is one of the most demanding jobs. We examined the obstacles and conflict scenarios that contemporary coaches must deal with, the skills they need to properly carry out their duties, and how to inspire athletes to reach their maximum potential. There are numerous renowned Trainers available to instruct the prospects. Additionally, it offers a joyful and safe atmosphere that enables everyone to improve their level of fitness. Here, candidates have the chance to compete in a variety of events held in the gym.